MÖBIUS-INVARIANT DIVISORS FOR THE SPACE $A^p_{α}$ - Mikaelyan, G.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the paper we introduce new Mӧbius-invariant and efficient divisors for $A^p_{α}$ spaces. The method of construction of new divisors is shown.
Keywords: divisor; infinite product; Blaschke; Djrbashian space